Super-enhancer-associated SNHG15 cooperating with FOSL1 contributes to bladder cancer progression through the WNT pathway - Mingyue Tan; Qi Pan; Hua Gong; Xinyu Zhai; Zhong Wan; Minyao Ge; Jianyi Gu; Dingguo Zhang; Xia Chen; Dongliang Xu (Elsevier, 2023)
Small nucleolar RNA host gene 15 (SNHG15) plays an oncogenic role in many cancers. However, the role of SNHG15 in bladder cancer (BLCA) remains unclear. In this study, the regulation of SNHG15 on the activities of BLCA cells (T24 and RT112) was investigated. In detail, super-enhancers (SEs), differentially expressed genes, and functional enrichment were detected by bioinformatic analyses. Mutant cell lines lacking SNHG15-SEs were established using CRISPR-Cas9. Relative gene expression was detected by quantitative polymerase chain reaction (qPCR), western blot, in situ hybridization, and immunohistochemistry assays. Cell senescence, apoptosis, viability, and proliferation were measured. Chromatin immunoprecipitation (ChIP)-qPCR and luciferase reporter gene assays were conducted to analyze the interactions between genes. A novel super-enhancer of SNHG15 (SNHG15-SEs) was discovered in several BLCA datasets. The deletion of SNHG15-SEs resulted in a significant downregulation of SNHG15. Mechanistically, the core active region of SNHG15-SEs recruited the transcription factor FOSL1 to facilitate the SNHG15 transcription, thereby inducing the proliferation and metastasis of BLCA cells. Deletion of SNHG15-SEs inhibited the growth and metastasis of T24 and RT112 cells by inactivating the WNT/CTNNB1 pathway activation. Overexpression of FOSL1 in SNHG15-SEs restored the cell proliferation and metastasis. Next, a xenograft mouse model showed that SNHG15-SEs deletion inhibited the proliferation and metastasis of BLCA cells in vivo. Collectively, our data indicate that SNHG15-SEs recruit FOSL1 to promote the expression of SNHG15 which interacts with CTNNB1 in the nucleus to activate the transcription of ADAM12, leading to the malignance of BLCA cells.